Sistem Media Massa Indonesia di Era Reformasi: Perspektif Teori Normatif Media Massa - Syam, Nia Kurnaiti (FIkom Unisba, 2006)
Social control as a means of mass media becomes very crucial in a democratic country. Within this function, mass media has positioned itself to control executive decisions in development process. But the functions of mass media are much more than to be a watchdog. As explored by this article, many theories concerning mass media functions from normative perspective are formulated by mass communication scholars. There are at least 6 (six) theories concerning mass media system through which the function of mass media is derived: (1) Authoritarian; (2) Free Press; (3) Social Responsibility; (4) Soviet Press; (5) Development Press; (6) Democratic-Participant. As for Indonesia, in order to achieve national goals based on democratic process, the press system must develop in ways that respected the diversity of multicultural perspective and public opinion pluralism.